2019
DOI: 10.1111/jcmm.14857
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bromodomain and extra‐terminal proteins increases sensitivity to venetoclax in chronic lymphocytic leukaemia

Abstract: The newest drugs to target chronic lymphocytic leukaemia (CLL) include the inhibitors of the intracellular B-cell receptor signalling (BCR inhibitor) 1 and the BCL2 inhibitor venetoclax. 2,3 B-cell receptor signalling inhibitors incorporate the direct BTK inhibitor ibrutinib and the inhibitor of PI3K-delta, 4 a BTK downstream effector, idelalisib. Both ibrutinib and idelalisib have entered the clinical field with impressive results in chemotherapy-refractory CLL patients. However, both drugs are less effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Similarly, we found that MEC1 or MEC1-ROR1 cells transfected to express high levels of BCL2 WT , BCL2 A113P , or BCL2 G101V also had reduced sensitivity to venetoclax compared to the parent MEC1 or MEC1-ROR1 cells. Despite the noted resistance of MEC1 cells to venetoclax [ 45 ], we still found that MEC1-ROR1 were even less sensitive to this drug, indicating that the expression of ROR1 per se can enhance drug resistance.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similarly, we found that MEC1 or MEC1-ROR1 cells transfected to express high levels of BCL2 WT , BCL2 A113P , or BCL2 G101V also had reduced sensitivity to venetoclax compared to the parent MEC1 or MEC1-ROR1 cells. Despite the noted resistance of MEC1 cells to venetoclax [ 45 ], we still found that MEC1-ROR1 were even less sensitive to this drug, indicating that the expression of ROR1 per se can enhance drug resistance.…”
Section: Discussioncontrasting
confidence: 56%
“…MEC1 leukemia cells already are relatively resistant to venetoclax compared to the primary leukemia cells of patients with CLL [ 45 ]. Nonetheless, we examined whether the expression of ROR1 could enhance the resistance of this cell line to venetoclax in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a wide range of BETi have now been tested together with various BH3-mimetics, though most studies have focussed on Venetoclax where enhanced responses from combining the drugs have been seen in vitro and in vivo in many haematological malignancies including T cell lymphoma, CLL, T cell acute lymphoblastic leukaemia, and diffuse large B cell lymphoma [ 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 ], and some solid tumours such as small cell lung cancer [ 298 ]. The dual BCL-XL/BCL-2 inhibitor Navitoclax was also shown to synergise with BETi in small cell lung cancer, colorectal cancer, glioma and B-cell lymphomas [ 299 , 300 , 301 , 302 ], whilst BH3-mimetics targeting MCL-1 enhance BETi activity in AML and melanoma [ 292 , 303 ].…”
Section: Therapeutic Strategies Targeting Bcl-2 and Mycmentioning
confidence: 99%
“…Despite the remarkable preclinical activity of BET inhibitors in hematological malignancies, studies to identify beneficial combination therapy approaches to enhance efficacy have been reported [31]. As expected, synergism was observed when combining BET inhibitors (e.g., BAY 1238097, GS-5829, OTX015) with inhibitors of BTK (ibrutinib), SYK (entospletinib), PI3K (copanlisib, idelalisib), or BCL2 (venetoclax) in preclinical models of CLL [32][33][34] and DLBCL-RT [35]. Interestingly, the anti-leukemic activity of BET inhibitor, GS-5829, proved to be synergistic in combination with ibrutinib or idelalisib in primary CLL / nurse-like cell co-cultures reflective of the LN TME in CLL [32].…”
Section: Introductionmentioning
confidence: 90%